Novel Small Molecule Inhibitors Of PTP1B - M.V.V.V.SEKHAR REDDY; G.CHAKSHUSMATHI; M.LAKSHMI NARASU (International Journal of Pharma and Bio Sciences, 2012)
Protein tyrosine phosphatase is a classical non receptor tyrosine phosphotase enzyme and is an important regulator in several signaling pathways including insulin and leptin. PTP1B is a negative regulator of insulin receptor (IR) which dephosphorylates tyrosine residues of Insulin Receptor tyrosine Kinase (IRK) domain and induces resistance to insulin sensitivity and obesity up on over expression of PTP1B. Thus PTP1B is a vital therapeutic target for Type II diabetes and developing a selective PTP1B inhibitor is an essential breakthrough in controlling the disease which has been afflicting 1/3rd of world population. We have identified few small molecule PTP1B inhibitors which have shown micro molar range inhibition by in vitro pNPP assay method.